Study on Traditional Hair Oil in The Management of Depression - Sritharan, A.; Sritharan, G. (International Conference on Ayurveda, Unani, Siddha & Traditional Medicine 2014 Clinical Studies, 2014)
Depression may be a symptom of stressful lifestyle of depressive illness, anxiety disorders, any psychiatric conditions or any other pathological conditions. The doctors prescribe different types of tranquilizers for the management of depression. Even though the tranquilizers initially give considerable relief from depression but continuous long term use may induce various toxic ef- fects. In such a scenario there is an immediate need for the management of depression in a natural way. The study was conducted in 30 clinically diagnosed patients of depression who were willing to give informed consent. The study was conducted at Jaffna, Sri Lanka. The age group of 20-60 years of both sexes having depression duration was selected randomly for the study. Patients of depression and anxiety disorders without any complication of any other diseases were included for the study. A proposed herbal formulation "Paruththi Elaich sartu oil (Gossypium indica leaves juice oil)" and "churnum (powder)" was selected. The drug selected for the study was mainly had in folk remedy of Jaffna Sri Lanka. Traditional physicians use this oil for depressive condi- tion without scientific evaluation. Three groups of 10 patients from each group. Group-I: 30 ml "Paruthi Ilaich sartu oil" hair oil once daily for a period of 3 months with gentle massage to the entire scalp. Group - II: churnum (powder) in the dose of 3 gms per day (two times) with- luke warm milk for a period of 3 months. Group - III: both churnum and"Paruthi Ilaich sartu oil" hair oil simultaneously inthe dose and scheduled as discussed above. Depression were assessed before and after the therapy by yawning, drowsiness, malaise, fatigue & inertness, headache, lack of concentration, lose of memory, poor sensory perception, indigestion, constipation, weight loss and loss of luster. Regarding overall improvement in clinical features of depression the results were highly significant (p<0.01). The herbal formulation is safe, without any adverse effects, economical and effective remedy for the management of depression. In combined therapy, groups have synergistic effects in the management of depression and the results were better.
Keywords: Paruthi Ilaich sartu oil; Churnum; Depression